Assessing preferences of potential visitors for nature-based experiences in protected areas. (October 2017) - Moyle, Brent D.; Scherrer, Pascal; Weiler, Betty; Wilson, Erica; Caldicott, Rod; Nielsen, Noah
Abstract: Visitor experiences have been identified as critical for the sustainable management of tourism destinations. However, researchers have given limited attention to how to measure visitor preferences for different, newly proposed experiences, especially in nature-based tourism contexts. This paper aims to capture potential visitors' preferences for nature-based visitor experiences that would alleviate pressure on the iconic summit of Mount Warning, Australia. Findings reveal a preference for passive rather than active experiences. Consistency between the four measurement approaches used was high. Future studies should consider adopting multiple measures to underpin evidence-based management that informs the design of nature-based tourism experiences. Highlights: Identifies how to disperse visitors from an iconic natural attraction by designing alternative experiences. Integrates potential visitor preferences into the design of nature-based tourism experiences. Uses visitors' likelihood of choosing a scenario to assess relative preferences for nature-based tourism experiences. Finds the current iconic experience to be potential visitors' least-preferred scenario. Compares the relative merits of four measurement approaches for assessing visitor preferences.